Determinants of User Satisfaction with a Mobile Application Using the Extended Webqual 4.0 Method and Structural Equation Modelling: A Case of the PLN Mobile Application - Andi Saputra; Dedi I. Inan; Ratna Juita; Marlinda Sanglise; Muhamad Indra (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
In the era of rapid technological growth, people increasingly expect convenience in all aspects of life, including how they interact with public services. The PLN Mobile application, developed by PT PLN (Persero), aims to facilitate access to information and services for the community. However, many users have provided low ratings and negative feedback. The purpose of this research is to analyze the factors influencing user satisfaction with the PLN Mobile application, using the Webqual 4.0 method. A total of 101 respondents were selected using a purposive sampling technique, and the data were analyzed using Structural Equation Modeling (SEM). The findings reveal that Usability, System Quality, Information Quality, and Interaction Quality significantly affect user satisfaction, while Service Quality does not. This indicates that the application meets most user expectations, though there is still potential for further improvement. These findings offer theoretical contributions to the Webqual 4.0 method and practical insights for developers to enhance the application and improve user satisfaction.